Attitude Towards Advertising: From Malaysians And Indonesians Perspectives - Hiram, Ting; Ernest Cyril, de Run; Sudiyanti, Sudiyanti; Cheah, Jun-Hwa (2016)
This study seeks to determine attitude towards advertising in general in Malaysia and Indonesia, and the moderating effect of nationality on behavioural relationships. Theory of reasoned action and the seven-factor belief model are utilized to explain the effect of advertising beliefs on attitude and subsequently intention. Since little study is done to compare advertising attitudes in the Southeast Asian context, multi-group analysis using variance-based structural equation modeling is used to investigate the subject matter between the two countries. Online questionnaire was administered, and 215 Malaysians and 147 Indonesians responded in two months. The findings show Malaysians and Indonesians share similar beliefs, attitude and intention towards advertising except for the belief about materialism. The effect of such belief is also found to be significantly different between them. Despite being largely similar in advertising attitude, it is pivotal to distinguish their advertising beliefs. The study lays foundations for further cross-border investigation in ASEAN.